2015
DOI: 10.1002/14651858.cd004307.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Incentives for smoking cessation

Abstract: Incentives appear to boost cessation rates while they are in place. The two trials recruiting from work sites that achieved sustained success rates beyond the reward schedule concentrated their resources into substantial cash payments for abstinence. Such an approach may only be feasible where independently-funded smoking cessation programmes are already available, and within a relatively affluent and educated population. Deposit-refund trials can suffer from relatively low rates of uptake, but those who do si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
150
0
13

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(177 citation statements)
references
References 180 publications
10
150
0
13
Order By: Relevance
“…6,7 Others are based on financial incentives [8][9][10] and nicotine replacement therapy. [11][12][13] While some of these interventions have improved cessation during pregnancy, they lack effectiveness for the prevention of postpartum relapse.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Others are based on financial incentives [8][9][10] and nicotine replacement therapy. [11][12][13] While some of these interventions have improved cessation during pregnancy, they lack effectiveness for the prevention of postpartum relapse.…”
Section: Introductionmentioning
confidence: 99%
“…Cash and vouchers as incentives are widely used to encourage smokers to quit. [33] Data were entered into SPSS-Version 20. Normality of data was examined.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, direct financial incentives to patients also improve rates of smoking cessation, at least for as long as the incentives are in place. 4 These incentives are typically provided by either the employer or the patient's health insurance carrier. Other studies have found that gaining insurance coverage leads to reduced rates of smoking.…”
mentioning
confidence: 99%